How Do Antihypertensive Drugs Work? Insights from Studies of the Renal Regulation of Arterial Blood Pressure - Digne-Malcolm, Holly; Frise, Matthew C.; Dorrington, Keith L. (Frontiers in Physiology, 2016)
Though antihypertensive drugs have been in use for many decades, the mechanisms by which they act chronically to reduce blood pressure remain unclear. Over long periods, mean arterial blood pressure must match the perfusion pressure necessary for the kidney to achieve its role in eliminating the daily intake of salt and water. It follows that the kidney is the most likely target for the action of most effective antihypertensive agents used chronically in clinical practice today. Here we review the long-term renal actions of antihypertensive agents in human studies and find three different mechanisms of action for the drugs investigated. (i) Selective vasodilatation of the renal afferent arteriole (prazosin, indoramin, clonidine, moxonidine, α-methyldopa, some Ca++-channel blockers, angiotensin-receptor blockers, atenolol, metoprolol, bisoprolol, labetolol, hydrochlorothiazide, and furosemide). (ii) Inhibition of tubular solute reabsorption (propranolol, nadolol, oxprenolol, and indapamide). (iii) A combination of these first two mechanisms (amlodipine, nifedipine and ACE-inhibitors). These findings provide insights into the actions of anti-hypertensive drugs, and challenge misconceptions about the mechanisms underlying the therapeutic efficacy of many of the agents.